World Workshop on Oral Medicine VII: Relative frequency of oral mucosal lesions in children, a scoping review. (29th May 2019) - Hong, Catherine H. L.; Dean, David R.; Hull, Katrusha; Hu, Shi Jia; Sim, Yu Fan; Nadeau, Christine; Gonçalves, Sandra; Lodi, Giovanni; Hodgson, Tim A.
Abstract: Objective: To detail a scoping review on the global and regional relative frequencies of oral mucosal disorders in the children based on both clinical studies and those reported from biopsy records. Materials and Methods: A literature search was completed from 1 January 1990 to 31 December 2018 using PubMed and EMBASE. Results: Twenty clinical studies (sample size: 85, 976) and 34 studies from biopsy services (40, 522 biopsies) were included. Clinically, the most frequent conditions were aphthous ulcerations (1.82%), trauma‐associated lesions (1.33%) and herpes simplex virus (HSV)‐associated lesions (1.33%). Overall, the most commonly biopsied lesions were mucoceles (17.12%), fibrous lesions (9.06%) and pyogenic granuloma (4.87%). By WHO geographic region, the pooled relative frequencies of the most common oral lesions were similar between regions in both clinical and biopsy studies. Across regions, geographic tongue (migratory glossitis), HSV lesions, fissured tongue and trauma‐associated ulcers were the most commonly reported paediatric oral mucosal lesions in clinical studies, while mucoceles, fibrous lesions and pyogenic granuloma were the most commonly biopsied lesions. Conclusions: The scoping review suggests data from the clinical studies and biopsy records shared similarities in the most commonly observed mucosal lesions in children across regions. In addition, the majority of lesions were benign in nature.